2021
DOI: 10.3390/toxins13020154
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Transcriptomic Techniques to Decipher the Molecular Evolution of Venoms

Abstract: Nature’s library of venoms is a vast and untapped resource that has the potential of becoming the source of a wide variety of new drugs and therapeutics. The discovery of these valuable molecules, hidden in diverse collections of different venoms, requires highly specific genetic and proteomic sequencing techniques. These have been used to sequence a variety of venom glands from species ranging from snakes to scorpions, and some marine species. In addition to identifying toxin sequences, these techniques have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 119 publications
(162 reference statements)
0
11
0
Order By: Relevance
“…The investigation of venom diversity is strongly multidisciplinary, in which omics technologies, including genomics, transcriptomics, and proteomics, play an increasingly large role in the field of venom research [ 43 , 44 ]. Nowadays, the bottom-up (BU) and the top-down (TD) approach have become the gold standard in snake venom proteomics and the advantages and disadvantages of both have been extensively discussed [ 45 , 46 , 47 , 48 , 49 , 50 ]. The integration of high-resolution mass spectrometry (MS)-based workflows, mostly in combination with preceding decomplexation steps, plays a decisive role and has continuously developed over the past decades [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of venom diversity is strongly multidisciplinary, in which omics technologies, including genomics, transcriptomics, and proteomics, play an increasingly large role in the field of venom research [ 43 , 44 ]. Nowadays, the bottom-up (BU) and the top-down (TD) approach have become the gold standard in snake venom proteomics and the advantages and disadvantages of both have been extensively discussed [ 45 , 46 , 47 , 48 , 49 , 50 ]. The integration of high-resolution mass spectrometry (MS)-based workflows, mostly in combination with preceding decomplexation steps, plays a decisive role and has continuously developed over the past decades [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our mass spectrometry analysis revealed that the expression batch of USCTX was almost exclusively composed of peptide pairs displaying aberrant cysteine crosslinking or peptides that lack disulfide bonds. Only a single peptide with m / z 1215.56, matching the C2-C5 crosslink of native USCTX, was identified via MALDI and even more sensitive Orbitrap experiments [ 27 , 28 , 29 ]. Our data suggest that the cell-free system faces difficulties in facilitating the correct disulfide bond formation in such heavily cysteine-crosslinked peptides.…”
Section: Resultsmentioning
confidence: 99%
“…For mass spectrometry, we used the highly sensitive Orbitrap instrument on which we previously identified other ICK components [ 28 , 29 ]. Briefly, 0.5 µg of each sample in 0.1% formic acid (Sigma-Aldrich) was loaded onto a 50 cm µPAC C18 column (Pharma Fluidics, Gent, Belgium) mounted on an UltiMate 3000RSLCnano (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…The scientific community is capitalizing on many innovations to transform traditional approaches used for numerous toxic mitigation measures under aquatic environments. Related investigations have been introduced, such as Habschied [14], Mouchbahani-Constance et al [15], Peles et al [16], Reichwaldt et al [17], Sotnichenko et al [18], and so on.…”
Section: Discussion and Applicationmentioning
confidence: 99%